Recursos Simbólicos para la Revitalización de la Identidad Cultural de la Parroquia Santa Rosa, Cantón Ambato. - Escobar Santacruz, Andrea Estefanía (2017)
The present academic article has as main objective to find out which are the symbolic resources that affect in the cultural identity of the Santa Rosa Parish through the historical and collective memory. Among the contributions of the study are, in the first place, the alert about the forgetfulness of the past, that today the young santarroseños experience; And, secondly, the most representative symbolic resources are presented, with which the cultural identity of the sector is to be revitalized. It should be noted that through the application of the bibliographic review techniques, participant observation and interview were rescued as the most important symbolic resources of the parish: the Feast of the Three Wise Men, the feast of the Apparition of the Virgin of the Elevation (Patroness of the Diocese of Ambato), the commemoration of the Holy Week or Captaincy, the elaboration of the santarroseño bread, the shampoo, chicha de jora; And, within the sports and popular games is the table ball, the cycling, the cocos, the bowling and the capirotejo. With the processing and discernment of the information obtained, it was concluded that, instead of being interested in their own history and culture, the young people of the parish assimilate strange symbols and meanings, the product of globalization and modernity, without there being By the authorities some concern or actions to reverse this situation. Adding to this, immigration and the weak communication relationship between generations